Exploring Commuter’s Preferences and Future Intentions to Use Ride-Sharing: A Case Study From a Developing Country - Intizar Hussain; Qinaat Hussain; Charitha Dias; Walid Al Bargi; Nazam Ali; Muhammad Abdullah; Lin Cheng (Journal of Advanced Transportation, 2025)
This study investigates transportation choices with a specific focus on ride-sharing practices. The main aim of the study was to understand the current modes of transport, the primary reasons for choosing them, ride-sharing experiences, and future ride-sharing intentions within the context of Islamabad, Pakistan. The final analyses were based on 294 respondents, including 88 respondents with prior ride-sharing experience. The sample was skewed toward male participants (80.6%), reflecting national mobility patterns. Logistic regression was employed to investigate the relationship between different factors toward individuals’ intentions to use ride-sharing as a future commuting option. The results indicate that gender, previous ride-sharing experience, preferences for companionship during ride-sharing, and the primary mode of transportation for shopping emerged as significant factors influencing future ride-sharing intentions. Males are nearly three times more likely to adopt ride-sharing (Exp (β) = 2.9) than females (β = 1.07, p<0.01). Similarly, individuals with previous ride-sharing experience (β = 0.94, p<0.01) have a 2.6 times higher likelihood of choosing ride-sharing in the future. Moreover, respondents preferring larger groups while ride-sharing exhibit higher adoption intentions (β = 0.26, p=0.02, Exp (β) = 1.3). In contrast, individuals primarily using motorcycles (β = −1.53, p=0.02, Exp (β) = 0.2) or personal cars (β = −1.72, p=0.01, Exp (β) = 0.2) for shopping are less inclined to shift toward ride-sharing. The model achieves a Nagelkerke pseudo R2 of 0.23, explaining 23% of the variance in future ride-sharing intentions. This research yields valuable insights that could guide initiatives aimed at fostering ride-sharing adoption and encouraging individuals to utilize this mode of transportation.